Kadar prevalens kemurungan dan cubaan bunuh diri dalam kalangan remaja di Malaysia - Nor Ba’yah Abdul Kadir,; Diana Johan,; Nur Saadah Mohamad Aun,; Norhayati Ibrahim,; Hilwa Abdullah@Mohd. Nor, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Suicide attempts behavior among adolescents in Malaysia is notable and alarming. Usually, suicide attempts are associated with depression as one of the risk factors. This study attempted to identify the prevalence rate of depression and suicide attempts behavior among Malaysian adolescents. In this study, adolescents involved as the study’s sample are those who are aged between 13 to 24 years old. The instrument used to measure depressive symptoms and suicide attempts in this study is The Columbia Depression Scale for Adolescents. 22.3% and 20.5% of adolescents involved in this study showed depressive symptoms at a moderate level according to their age category which is early and late adolescents respectively. On the other hand, the prevalence rate of suicide attempts among Malaysian adolescents is 8.7%. Findings of this study could be a benchmark for future studies as well as direction for future planning in the prevention of suicidal behavior.